Review of Original Research, Processing Evolution, Chemical Constituents, and Pharmacological Effects of Semen Vaccariae - Yan-Feng Li; Ya-Shu Liu; Yuan-Liang Ai; Zheng Liu (World Journal of Traditional Chinese Medicine)
To review published literature, summarize information on the chemical composition and pharmacological effects of Semen Vaccariae (SV), and make it available for future researchers to understand the general research status of SV. The literature was collected from China National Knowledge Infrastructure, China Science and Technology Journal Database, Flora of China, PubMed, Google Scholar, Web of Science, PubChem, and other online databases. The result shows: SV contains flavonoid glycosides, triterpenoid saponins, volatile oils, cyclic peptides, phenolic acids, alkaloids, and other chemical components, and it has antitumor, anti-depression, anti-fibrosis, hypolipidemic, liver and lung injury protective and other effects. Currently, research on the chemical constituents and pharmacological effects of SV has made little progress; however, the understanding of specific therapeutic mechanisms of action on clinical conditions, such as cardiovascular, prostate, and osteoporosis remains to be improved. In addition, this study describes the plant origin and processing evolution of SV to understand SV more comprehensively.